Prediction and Prospection of Groundwater in the Iraqi Western Desert Using Remote Sensing and GIS (Iraqi National Journal of Earth Science (INJES), 2026)
Groundwater resources are receiving a lot of attention, especially in arid and semi-arid areas as a result of the growing demands for water brought on by urbanization, population growth, and agricultural development. Finding the most significant contributing parameters such as lineament density, frequency, and junction nodes that reveal the groundwater potential is the foundation of this investigation. To determine suitable sites for drilling wells, analysis of linear structures is necessary to detect and exploit groundwater sustainably. This study highlights the importance of geospatial systems including remote sensing and geographic information system technologies to effectively explore and manage groundwater resources. To identify linear structures in the study area, different image enhancement techniques are applied such as band composite (BC) and high pass filtering (HPF). These methods work well and they are suitable for identifying these structures. The results show that the area contains a large number of short and long fractures, most of which have an orientation from northwest to southeast, and that it is possible to explore groundwater in areas with a high density of areas with intersections in linear structures. The area, where groundwater occurrence is most promising for sustainable use of groundwater, has been identified within the region. Using remote sensing (RS) data and geographic information systems (GIS), a thematic map of each parameter is created. The final groundwater potential zones of the studied region are created by combining these input layers using the GIS Raster Calculate Module. Different groundwater prospective potential zones are depicted on the final output map: very high (49 km2), high (261 km2), and moderate (1041 km2).
Keywords: Groundwater, Lineaments, Iraqi Western Desert, Remote Sensing, GIS.